DENSITY BASED SMART TRAFFIC CONTROL SYSTEM USING CANNY EDGE DETECTION (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2025)
The need for state-of-the-art equipment and technology to enhance traffic management is become more pressing as the problem of urban traffic congestion deteriorates. empirical evidence has shown that the traditional methods, such as timers and human control, are inadequate in effectively tackling this problem. The present study introduces a traffic control system that employs digital image processing and intelligent edge identification to enable real-time measurement of vehicle density. In contrast to earlier systems, this high-performance traffic control system offers a significant improvement in response time, automation, vehicle management, reliability, and overall efficiency. Furthermore, the whole process, including picture collection, edge recognition, and green signal allocation, is documented with suitable schematics and validated by hardware implementation using four illustrative images of different traffic situations.